Intensity of free radical processes in the leaves of arboreal plants under act of industrial dust borne extracts - Piskova, Olga; Gryshko, Vitalii (Acta Agraria Debreceniensis, 2010)
The influence of industrial pollutants on the intensity of lipid peroxidation in the assimilatory organs of arboreal plant was investigated. The differential changes of the probed indexes are set depending on the species. Information is got can testify to participation of lipid peroxidation products in forming of reactions-answers of arboreal plants on influence of industrial dust borne extract with content of heavy metals. Determination of level and rates of accumulation of Zn, Ni, Pb and Cd, in the leaves of arboreal plants in the conditions of different contamination level allowed to take species to two groups. To the first (phytoextraction potential exceeds a base-line level in 10 times) belong Populus bolleana Lauche, P. italica (Du Roi) Moench, Picea pungens Engelm and Sorbus aucuparia L. To the second (exceeds a base-line level from 5 to 10 times) belong Acer negundo L., Aesculus hippocastanum L., Betula pendula Roth and Tilia cordata Mill. The most substantial increase of peroxidation secondary product content (more than in 2.5 times) is peculiar for B. pendula, A. hippocastanum and P. pungens Engelm., that well conforms to the rates of heavy metals translocation, it has however species-specific character.